Biomass Potential, Carbon Stock and Carbon Sequestration of Urban Forest in Shimla City of Himachal Pradesh, India - Supriya, Kalyani; Kapoor, Himesh; Thakur, Nishant (International Journal of Economic Plants, 2025)
The study was conducted during April–June month of 2022 at Shimla city of Himachal Pradesh, India under the facilities provided by Department of Environmental Sciences, HPU, Shimla to determine the carbon storage potential by urban forests in Shimla city, Himachal Pradesh. The biomass production and carbon sequestration of the urban forest across two altitude ranges (B1 and B2) and four aspects (A1, A2, A3, and A4) showed significant variation due to the aspects and altitudinal gradient. The results revealed the maximum biomass (625.61 t ha-1) was accumulated in A1, whereas in case of altitudinal range maximum biomass (530.98 t ha-1) in B2 (2100–2500 m). Vegetation carbon density of moist-temperate forest ecosystem followed the order; A1>A2>A3 and A4 aspect, whereas in case of altitudinal ranges the trend was B2>B1. Similar trend was also seen in respect of biomass carbon stock at different aspect and altitudinal range. Maximum soil organic carbon density was recorded in aspect (22.73 t ha-1), which was found to be significantly higher than all other. In case of the altitudinal range the trend was B1 (19.66 t ha-1) >B2 (17.06 t ha-1). There were 5 pre-dominant tree species identified in study area as Quercus leucotrichophora, Rhododendron arboretum, Cedrus deodara, Pinus roxburghii and Quercus floribunda which contributed in biomass production and carbon storage potential. For species contribution in biomass, Quercus leucotricophora has maximum contribution (742.48 t ha-1) among all other and similar observations in case of total carbon stock and total CO2 sequestrated, which were seen maximum in Quercus leucotricophora (371.24 t ha-1) and (1362.1650 t ha-1).